The General Data Dissemination System : Guide for Participants and Users. (Manuals and Guides, 2013)
This guide explains the nature and objectives of the General Data Dissemination System (GDDS), describes its operation, and provides practical guidance to IMF member countries on participation in the system. The GDDS provides members with a basic framework for a broader national statistical development strategy. It covers a set of statistics recognized to be essential for all countries for policymaking and analysis in an environment that increasingly requires relevant, comprehensive, accurate, and timely statistics available to the general public. The General Data Dissemination System: Guide for Participants and Users addresses the full range of issues critical for compiling and disseminating data and making explicit plans for improvement to align national procedures with best practices.